Infant observation at the heart of training. - Sternberg, Janine, ....- (London : Karnac, 2005)
The study of infant observation is widely used as part of training to become a psychoanalytic psychotherapist; the skills learned through infant observation can be widely applied to practicing analysis with all ages. Through the delineation of the views of writers and teachers of infant observation and her own empirical research, Janine Sternberg addresses the reasons why infant observation is a vital part of training for all analysts.
Keywords: Observatietechnieken; Psychoanalyse; Psychotherapie